Relationship Between Kindergarten Teachers’ Accounts and Learners’ Performance - Juvina D. Costelo (East Asian Journal of Multidisciplinary Research, 2023)
The study was undertaken to ascertain the relationship between the Kindergarten Teachers’ Accounts and Learners’ Performance in different kindergarten classes of Palompon North District, through the descriptive-correlational design. Specifically, it looked into the profile or accounts of the kindergarten teachers and the performance of the learners on the seven developmental domains. Kindergarten teachers experience different challenges in the classroom as they take their roles and responsibilities, but through their positive perspective towards their profession and love for teaching they achieve equal opportunities for young children they work with. Fifteen teachers, shared their life episodes of challenges and opportunities they meet along the way as kindergarten teachers. Challenges were themed as (1) Curriculum, (2) Physical Environment, (3) Instruction and (4) Social Context. The result of the study would inspire kindergarten teachers to improve their teaching skills and widen their understanding on child development to provide appropriate and ultimate learning experience, exposed them to the joy of learning and give them the foundation for a lifelong process.